The Role of Human Capital Aspects as Sustainable Revenue in the Public Sector of the Singaraja District Court Office - Budiasni, Ni Wayan Novi; Putri, Made Budi Aryati Laksmi; Sarbaeni, Sarbaeni (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This research wants to examine more about human capital through aspects of training, work motivation, career development and job satisfaction on employee performance at the Singaraja District Court Office. The research was conducted using quantitative methods to measure the influence and the level of significance. The analysis tool uses the PLS SEM and after testing the inner and outer models it is found that the variables of training, work motivation, career development, job satisfaction have a positive and significant effect on employee performance, directly or indirectly. Job satisfaction as an intervening variable also has positive and significant implications. This condition indicates that human capital through aspects of training, work motivation, career development and job satisfaction on employee performance really needs further attention at the Singaraja District Court Office.